Роль цикла оксида азота в формировании особенностей течения рака яичника = Role of nitrogen oxide cycle in the formation features of the current ovarian cancer - Ribin, A. (Journal of Education, Health and Sport, 2015)
Ribin A. Роль цикла оксида азота в формировании особенностей течения рака яичника = Role of nitrogen oxide cycle in the formation features of the current ovarian cancer. Journal of Education, Health and Sport. 2015;5(11):399-404. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.34224 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2811%29%3A399-404 https://pbn.nauka.gov.pl/works/672048 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.09.2015. Revised 25.10.2015. Accepted: 20.11.2015. РОЛЬ ЦИКЛА ОКСИДА АЗОТА В ФОРМИРОВАНИИ ОСОБЕННОСТЕЙ ТЕЧЕНИЯ РАКА ЯИЧНИКА Role of nitrogen oxide cycle in the Formation FEATURES OF THE CURRENT ovarian cancer А. Рыбин A. Ribin Одесский национальный медицинский университет Odessa national medical university Summary The authors studied the activity indicators of the state of nitrogen oxide cycle in 28 women diagnosed with ovarian cancer. According to the clinical course of the pathological process the author ranked the surveyed patients into three groups. The results showed that the exacerbation of the pathological process was accompanied by a decrease in the activity of NO synthase and inteksifikatsiey formation and accumulation in the body NOx (nitrate-nitrite). The author believes that the reduction in the intensity of the activities of nitrogen oxide cycle worsens controllability processor of life in the body of patients, and the increase in nitrite-nitrate is against this background may contribute to the formation of nitrosamines - toxic metabolites that can impair the body's resistance to external influences. Keywords: nitric oxide, ovarian cancer, nitrites, nitrates. Резюме Авторы исследовали состояние показателей активности цикла оксида азота у 28 женщин, у которых диагностирован рак яичника. По особенностям клинического течения патологического процесса автор ранжировал обследованных больных на три группы. Результаты исследований показали, что утяжеление течения патологического процесса сопровождалось снижением активности NО-синтазы и интексификацией образования и накоплением в организме NOx (нитрат-нитритов). Автор полагает, что снижение интенсивности деятельности цикла оксида азота ухудшает регулируемость процессор жизнедеятельности в организме больных, а увеличение объемов нитрит-нитратов на этом фоне может способствовать усиленному образованию нитрозоаминов – токсических метаболитов, ухудшающих устойчивость организма к внешним воздействиям. Ключевые слова: оксид азота, рак яичников, нитриты, нитраты.